PELAKSANAAN DISCHARGE PLANNING DI RUANG RAWAT INAP DEWASA RUMAH SAKIT DI RUTENG - Mariati, Lusia Henny; Simon, Maria Getrida; Handi, Heriberrtus (Jurnal Abdimas Bina Bangsa, 2024)
The patient's readiness to recover is a decisive factor in successful treatment at home and after being treated in the hospital. The role of nurses becomes crucial in preparing the patient for the recovery process. This activity aims to increase nurses' understanding and commitment to implementing discharge planning in patients, starting when the patient enters the hospital and continuing until the patient returns home. The implementation methods in the early stages are group discussions focused on nurses, followed by education on treatment according to the patient's condition using the educational media leaflet. The results of this activity are an improved understanding of the nurse about the benefits of implementing discharge planning for the patient, produced media educational leaflets, and recommendations of standard operational procedures for executing the discharge planning